(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The Bidirectional Inter-Allied Converter (BIAC) is a key component of hybrid AC/DC microgrids as a bridge unit that facilitates power transfer between AC and DC subgrids. Instead of using a single BIAC, a power management strategy for the BIAC community is suggested as an extension of the concept of power sharing. To create the proper power references, a well-designed localised distributed fuzzy logic controller (LDFLC) is assigned to each BIAC in this control method. Each subgrid’s rated capacity determines how much electricity is allocated to it, which significantly enhances dependability and scalability. The Matlab/Simulink platform, which is used to test the stability analysis of the power management plan, also incorporates the concepts of balanced power sharing, bidirectional power flow, and communication time delay. A power management controller is recommended in this paper In order to increase efficiency in the hybrid distributed generating system, Bidirectional Inter-Allied Converter (BIAC) is constructed using LDFLC and compared to Proportional Integral based localised distributed controller (PILDC).